HUBUNGAN PENGGUNAAN GADGET, PEMBERIAN STIMULASI DAN STATUS PEKERJAAN IBU TERHADAP PERKEMBANGAN BAHASA ANAK USIA 1-3 TAHUN - Yulia Afwinda Saputri; Afdal; Nita Afriani; Asrawati; Yantri Maputra; Husna Yetti (LPPM Universitas Abdurrab, 2026)
Introduction : Language development in children aged 1-3 years is a critical foundation for learning readiness and social interaction. Language disorders or delays are a significant public health problem, with risk factors such as inappropriate gadget use, lack of early stimulation, and parenting dynamics influenced by maternal employment status. Objective : To determine the relationship between gadget use, stimulation provision, and maternal employment status on the language development of children aged 1-3 years at the Koto Panjang Ikua Koto Public Health Center, Padang City. Method : This study employed a cross-sectional design. A sample of 75 children aged 1-3 years was selected using two-stage sampling (simple random sampling to select 10 posyandu, followed by consecutive sampling). Data were collected through observation of language development using the Denver II instrument and interviews using a questionnaire. Results : The results showed that the proportion of children with delayed language development was 37.3%. There was a significant relationship between gadget use and language development (p=0.000) with a 54.6 times greater risk, and between stimulation provision and language development (p=0.000) with a 184.5 times greater risk. However, there was no significant relationship between maternal employment status and children's language development (p=0.898). Recommendation : Health workers are expected to intensify education about the negative impacts of gadgets and the importance of quality language stimulation. Parents are advised to limit the duration of gadget use and improve the quality of interaction and verbal stimulation consistently according to the child's developmental stages.